Erythema Annulare Centrifugum (Deep Type): A Rare Case Report - Khalid Al Hawsawi; Hanadi Alzanbagi; Sara Almatrafi; Samaher Refae; Fatmah Al-Shahrani; Hatem Alsulimani; Randa Almatrafi (Dermatology, 2017)
Erythema annulare centrifugum (EAC) is one of the figurate erythemas. It is uncommon inflammatory condition characterized by annular or arcuate erythematous eruptions that slowly enlarge centrifugally. It persists from few days to several months. It can recurrent. Here in we present a 40-year-old-male otherwise healthy, is working as a nurse in leprosy hospital. He was concerned from having leprosy. He developed recurrent asymptomatic skin lesions on his face for the last 5 months. The lesions start as small pimples that are getting bigger every day. The lesions last for few weeks and then disappear but recur again after weeks to months. Sensation examination of the facial skin was normal. On palpation of periauricular nerves, there was nerve hypertrophy. His older brother had similar skin lesions 10 years ago that lasted for few months and then healed without treatment. Skin examination revealed multiple non-scaly annular erythematous plaques, with variable sizes ranging from 2 cm to 4 cm on his face. Skin biopsy showed normal epidermis. The dermis showed moderately dense perivascular and periadnexal mononuclear cellular infiltrate in coat sleeve pattern in both upper and lower dermis. Fite stain was negative. The patient was reassured.